Penetapan Nasab Anak, Hukum Isla Penetapan Konstitusi dan Hukum Islam Terkait Tes DNA Sebagai Dalil Keabsahan Anak - Afifah, Afifah; Andar Yuni, Lilik (Maqasid: Jurnal Studi Hukum Islam, 2024)
This research aims to find out the basis of Islamic and state law related to the use of DNA tests as an argument for the validity of a child legitimacy. And to find out the application of DNA tests in resolving cases of determination based in Indonesia. This research uses normative legal and library research using a legislative research approach as the basis for legal theory. The results show that DNA tests can be used as evidence of determining the child’s lineage to his father. The method of determining lineage in Islamic law is determined in four ways; al-firasy, al-iqrar, al-bayyinah, and al-Qiyafah. Of these four methods, DNA testing is the latest evidence that has been developed with technology used as a means of determining the suitability of a person's lineage beyond the al-Qiyafah method. In Indonesian law, DNA tests have been recognized as renewable evidence in determining the lineage of children so that cases of children born from victims of rape, underhand marriage, and unregistered marriage can claim the right to maintenance and even lineage to their father.